Reformy wspólnej polityki rolnej i ich wpływ na rynek cukru w Polsce - Kraciuk, Jakub (Reforms of the Common Agricultural Policy and Their Influence on the Sugar Market in Poland, 2005)
The paper presents the principles of the sugar markets functioning in the European Union. It also shows expected changes on the sugar market in Poland, related to the currently introduced reforms of the common agricultural policy by our country.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 501-507